Manajemen Pembaharuan Pesantren di Tengah Tantangan Kehidupan Masyarakat Global - AFIFUL HAIR, MOH (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2016)
Pesantren as education institute obliged to perform a renewal refitalisation and utilize to yield taft generations, well informed generation with strength soul of pesantren firmness and develop knowledge which remain to coming from alqur'an and hadis. In growth of era, pesantren in this time deal with globalization current and modernization marked swiftly fast of technology and information. In consequence, pesantren have to make a change format, form, education method and orientation with note do not change vision, orientation and mission of pesantren